PENGARUH TINGKAT KESULITAN KEUANGAN PERUSAHAAN TERHADAP HUBUNGAN ANTARA KONFLIK KEPENTINGAN DAN KONSERVATISMA AKUNTANSI - Dina Rohana Kusumawati; Barbara Gunawan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2008)
The aim of this research is to examine the effect of interest conflict on accounting conservatism and the effect of company’s financial distress on the positive relation between interest conflict and accounting conservatism. The sample of this research was extracted with purposive sampling method. The populations of this research are all of the manufacturing company, which are listed at Indonesian Stock Exchange (IDX). The 216 corporate financial statements were analyzed as a sample. The technique for examining hypothesis is simple regression analysis to examining the first hypothesis and Moderated Regression Analysis (MRA) to examining the second hypothesis by using SPSS 16.00 program. The results of the research show that: firstly, interest conflict has a significant positive effect on accounting conservatism. And the secondly, company’s financial distress have a significant positive effect on the positive relation between interest conflict and accounting conservatism.